Chemical Profiling and Biological Activities on Nepalese Medicinal Plant Extracts and Isolation of Active Fraction of Nyctanthes arbor-tristis - Anita Khadka; Akash Budha Magar; Khaga Raj Sharma (The Scientific World Journal)
The importance of medicinal plants for the treatment of different diseases is high from the aspects of the pharmaceutical industry and traditional healers. The present study involves nine different medicinal plants, namely, Neolamarckia cadamba, Nyctanthes arbor-tristis, Pogostemon benghalensis, Equisetum debile, Litsea monopetala, Spilanthes uliginosa, Desmostachya bipinnata, Mallotus philippensis, and Phoenix humilis, collected from Chitwan district of Nepal for biochemical analysis followed by the isolation of active plant fractions from the bioactive plant extract. The methanolic extracts of roots, barks, seeds, seed cover, and the other aerial parts of plants were used for the phytochemical analysis and biological activities. The DPPH (2,2-diphenyl-1-picrylhydrazyl) free radical scavenging assay was adopted to evaluate the antioxidant activity. Antibacterial activity was evaluated using the agar well diffusion method. The antidiabetic activity was studied by the α-amylase enzyme inhibition assay. The highest antioxidant activity was observed in extracts of Nyctanthes arbor-tristis followed by Mallotus philippensis (seed cover), Pogostemon benghalensis, Litsea monopetala, Phoenix humilis, and Neolamarckia cadamba with IC50 values of 27.38 ± 1.35, 32.08 ± 2.81, 32.75 ± 2.13, 33.82 ± 1.07, 40.14 ± 0.93, and 50.44 ± 3.75 µg/mL, respectively. The highest antidiabetic activity was observed in extracts of Phoenix humilis followed by Desmostachya bipinnata and Pogostemon benghalensis with IC50 values of 95.69 ± 6.97, 99.24 ± 12.6, and 106.3 ± 12.89 µg/mL, respectively. The mild α-amylase enzyme inhibition was found in extracts of Nyctanthes arbor-tristis, Spilanthes uliginosa Swartz, Litsea monopetala, and Equisetum debile showing IC50 values of 110.4 ± 7.78, 115.98 ± 10.24, 149.83 ± 8.3, and 196.45 ± 6.04 µg/mL, whereas Mallotus Philippensis (seed cover), Mallotus philippensis (seed), and Desmostachya bipinnata showed weak α-amylase inhibition with IC50 values of 208.87 ± 1.76, 215.41 ± 2.09, and 238.89 ± 9.27 µg/mL, respectively. The extract of Nyctanthes arbor-tristis showed high zones of inhibition against S. aureus (ATCC 25923) and E. coli (ATCC 25922) of ZOI 26 and 22 mm, respectively. The chemical constituents isolated from the active plant Nyctanthes arbor-tristis were subjected to GCMS analysis where the major chemical compounds were 11,14,17-eicosatrienoic acid and methyl ester. These results support the partial scientific validation for the traditional uses of these medicinal plants in the treatment of diabetes and infectious diseases by the people living in different communities of Chitwan, Nepal.